Peningkatan Kemampuan Membaca Intensif Bahasa Indonesia dengan Menerapkan Model Pembelajaran Cooperative Script - Musfiana, Ardiyani; Kamto, Kamto (Sekolah Tinggi Agama Islam Pati, 2023)
This study aims to determine how to improve the ability of intensive reading of Indonesian language by applying the Cooperative Script learning model for fifth grade students of MI Sultan Agung 01 Sukolilo Pati. The practical benefit of this writing is as information to find out the improvement of children's intensive reading skills through the Cooperative Script learning model in grade V students of MI Sultan Agung 01 Sukolilo Pati. The theoretical benefits contribute to the development of educational science, especially in the application of learning models. This type of writing uses Classroom Action Writing (PTK) with the stages of planning, implementation, observation and reflection. The implementation of writing was carried out in 2 cycles taking the location of MI Sultan Agung 01 Sukolilo Pati. The writing was done collaboratively between the Indonesian language teacher and the author. The subjects of this writing are fifth grade students of MI Sultan Agung 01 Sukolilo Pati with a total of 29 students. Data collection techniques used observation sheets, tests, documentation and field notes. The data analysis technique in this writing is a mixture of descriptive qualitative and descriptive quantitative. The conclusion of this writing shows that by applying Cooperative Script Learning Model can improve the ability of intensive reading in class V (Five). It can be seen from the average score of learning outcomes in the pre-cycle of 67.75 with low criteria increased to 78.51 with high criteria in cycle I and increased again in cycle II by 86.06 with high criteria. While the percentage of completeness from 34.49% with very low criteria in the pre-cycle increased to 72.41% with high criteria in cycle 1 and increased again in cycle II by 89.65% with very high criteria. Thus, the Cooperative Script learning model can be used to improve intensive reading skills.